Partition’s Shadow: - Debjani Sengupta (Crossings, 2023)
Assam’s Barak Valley is an example of how the 1947 Partition of India and Pakistan left behind long-term conflicts and issues  pertaining to identity, place, and belonging that have created turmoil in the geo-political space that we refer to as India’s Northeast. The transformation of this space from a frontier during colonial times to a borderland in 1947 is not only significant for the genealogy and configuration of states within the region but also because this understanding subverts common assumptions about 1947, particularly on issues of communal polarizations, the formation of the border as well as the participation of non- political groups like the tribal populations who had very little stake in the playing out of the Radcliffe Line. Siddhartha Deb’s 2002 novel The Point of Return looks at some of these questions of identity and belonging that so plague the region. The novel is an exploration of the life journeys of Dr. Dam and his son Babu and their relationship to the geographical locations they come to inhabit. The spatial and temporal realities that came into being in the Northeastern region is charted through this text in the postcolonial state making practices that produce irreversible patterns of social and political chaos. Issues of ethnicity, language, and belonging that are contentious questions in this region are represented in this narrative as the continued precarity of people who had come to live here. This essay presents an analysis of the novel through the optics of history and literature, using tools from the Phenomenological analysis of Time by Paul Ricouer, to investigate how the interface of events and memory transform and complicate our understandings of a contentious divided past.